SS433's circumbinary ring and accretion disc viewed through its attenuating disc wind - Perez, S; Blundell, K (2010)
We present optical spectroscopy of the microquasar SS433 covering a significant fraction of a precessional cycle of its jet axis. The components of the prominent stationary H-alpha and H-beta lines are mainly identified as arising from three emitting regions: (i) a super-Eddington accretion disc wind, in the form of a broad component accounting for most of the mass loss from the system, (ii) a circumbinary disc of material that we presume is being excreted through the binary's L2 point, and (iii) the accretion disc itself as two remarkably persistent components. The accretion disc components move with a Keplerian velocity of ~600 km/s in the outer region of the disc. A direct result of this decomposition is the determination of the accretion disc size, whose outer radius attains ~8 R_sun in the case of Keplerian orbits around a black hole mass of 10 M_sun. We determine an upper limit for the accretion disc inner to outer radius ratio in SS433, R_in/R_out ~ 0.2, independent of the mass of the compact object. The Balmer decrements, H-alpha/H-beta, are extracted from the appropriate stationary emission lines for each component of the system. The physical parameters of the gaseous components are derived. The circumbinary ring decrement seems to be quite constant throughout precessional phase, implying a constant electron density of log N_e(cm^-3) ~ 11.5 for the circumbinary disc. The accretion disc wind shows a larger change in its decrements exhibiting a clear dependence on precessional phase, implying a sinusoid variation in its electron density log N_e(cm^-3) along our line-of-sight between 10 and 13. This dependence of density on direction suggests that the accretion disc wind is polloidal in nature.